Indonesian Government’s Policy in Managing Chinese Foreign Direct Investment for Sustainable Transport Development - Haniyah Nurafifah; Virtuous Setyaka; Diah Anggraini Austin (Journal of Infrastructure Policy and Management, 2026)
Foreign Direct Investment (FDI) is one of the funding sources, alongside the State Budget (APBN), that can be used to support national development. This study aims to analyze the policies implemented by the Indonesian government to achieve adequate infrastructure development in accordance with the SDGs agenda, particularly transportation infrastructure that supports global sustainability by utilizing Chinese FDI as one of its funding sources. This study employs a qualitative approach with a descriptive research design. Primary data were obtained through interviews with the Ministry of Investment and Downstream Industry, while secondary data were collected from reports, journals, articles, and relevant websites. Using Theodore H. Moran’s concept of FDI and Development, this study analyzes how Indonesian government policies seek to achieve structural benefits in managing Chinese FDI in the transportation sector to support sustainable development. The findings show that the four main indicators of FDI and Development—transparency of payments, improvement of economic patterns, enhancement of the local business climate, and promotion of investment—have been implemented fairly well. Chinese FDI has contributed to technological transfer, skill upgrading, supporting industries, and improved investor confidence in Indonesia’s sustainable transportation development.